2009
DOI: 10.1016/j.ultsonch.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-transducer dual-frequency ultrasound generation to enhance acoustic cavitation

Abstract: Dual- or multiple-frequency ultrasound stimulation is capable of effectively enhancing the acoustic cavitation effect over single-frequency ultrasound. Potential application of this sonoreactor design has been widely proposed such as on sonoluminescence, sonochemistry enhancement, and transdermal drug release enhancement. All currently available sonoreactor designs employed multiple piezoelectric transducers for generating single-frequency ultrasonic waves separately and then these waves were mixed and interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…It was believed that the cavitation effect is more pronounced in the dual-frequency mode (16 and 40 kHz, and 25 and 40 kHz combinations), which was well presented in the work done by Tatake and Pandit in 2002 [9]. a cavitation zone with a higher bubble volume fraction (28 and 56 kHz, 28 and 100 kHz, and 28 and 200 kHz combinations) [10] and larger number of bubbles (83 and 241 kHz, and 83 and 271 kHz combinations) [11] were noticed in a dual-frequency sonoreactor, compared with mono-frequency sonoreactors. another possible explanation offered by lernetti et al in 1997 is the production of a larger number of air bubbles by the introduction of a low-frequency (20 kHz) stimulating field into a 700 kHz field, which aids the cavitation effect [12].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…It was believed that the cavitation effect is more pronounced in the dual-frequency mode (16 and 40 kHz, and 25 and 40 kHz combinations), which was well presented in the work done by Tatake and Pandit in 2002 [9]. a cavitation zone with a higher bubble volume fraction (28 and 56 kHz, 28 and 100 kHz, and 28 and 200 kHz combinations) [10] and larger number of bubbles (83 and 241 kHz, and 83 and 271 kHz combinations) [11] were noticed in a dual-frequency sonoreactor, compared with mono-frequency sonoreactors. another possible explanation offered by lernetti et al in 1997 is the production of a larger number of air bubbles by the introduction of a low-frequency (20 kHz) stimulating field into a 700 kHz field, which aids the cavitation effect [12].…”
Section: Introductionsupporting
confidence: 70%
“…Hence, more efficient tissue ablation can be achieved. Furthermore, nonlinear frequency mixing of multi-frequency ultrasound may locally reduce the cavitation threshold sufficiently for enhanced cavitation [30], [31]. another possible reason for this increase in efficiency may be that the radiation force inside the tissue contributes to the cavitation.…”
Section: F Discussionmentioning
confidence: 99%
“…Different frequency stimulation also contributes to a large variety of bubbles [34,35], which potentially enhances cell death by producing free radicals using a sonosensitizer drug [32]. It has been shown that inertial cavitation is enhanced during dual-frequency sonication, and when inertial cavitation is produced in a liquid, non-inertial cavitation occurs simultaneously [10,31]. This study describes an experimental approach using combined Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that dual-or multiple-frequency sonication extensively enhances the acoustic cavitation yield [10]. Using terephthalic acid dosimetry, Barati et al [11] showed that, with equal energies, the combination mode of sonication generated a fluorescence intensity that was approximately 1.5 times higher than the algebraic sum of sonication at 150 kHz and 1 MHz, and 3.5 times higher than sonication at each frequency alone.…”
Section: Introductionmentioning
confidence: 99%
“…We are actively investigating ways to enhance the current limitations through effective combination of frequencies during heating. Some approaches have already been proposed in the context of cavitation enhancement [69,70]. However, mechanisms behind mixed frequency ultrasound exposures such as the vibration of the transducer material or the effects in biological tissues are more complex.…”
Section: Discussionmentioning
confidence: 99%